Pengaruh Social Media Marketing Terhadap Brand Image Tour & Travel Hastuti Tour And Travel - Hastuti Indra Sari (LPPM Swadaya Institute of Business and Communication, 2021)
Tour & Travel Agent is an old type of business that can still maintain its potential as a business opportunity every year. This is due to the use of the internet, thus presenting the online travel market. One of the travel agency businesses that use the internet, especially social media, as a marketing medium to build a company brand image is Tour & Travel Hastuti. However, the growth of followers on the hastuti.sari@stieswadaya.ac.id Instagram account is relatively slow, and the level of follower engagement is still low. This study aims to find out how Tour & Travel Hastuti grows a positive brand image for followers of their Instagram account, hastuti.sari@stieswadaya.ac.id. In addition, to see the influence that social media has had on followers of brand images on their Instagram accounts. The method used in this research is quantitative with the type of associative survey research. The data technique uses analysis from observations, literature studies, interviews and questionnaires. The sample in this study was 96 followers of the hastuti.sari@stieswadaya.ac.id Instagram account. The sampling technique used non-probability sampling, namely purposive sampling. The data analysis technique used simple linear regression analysis. This study indicates a significant influence of social media on the brand image of followers of the hastuti.sari@stieswadaya.ac.id Instagram account, meaning that if the social media marketing variable is getting better, the brand image will be getting better.